Recuerdos del siglo XX - Lavrin, Asunción (Revista de Historia Social y de las Mentalidades, 2025)
This essay reviews key concepts in the education of women in the early twentieth century comparing the ideas of several educators in Spanish Ame rica and the debate over women as higher education. It analyzes the Gabriela Mistral Ìs educational ideas for women in her Lectura para mujeres and compares her to Mexican writer Rosario Castellanos. Finally, it urges rea d ers to create new models and concepts for women Ìs education in the twent i eth first century.
Keywords: Gender; Education; Latinamerican Women Ìs